(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Southwestern Atlantic margin is characterized by several canyon systems incised on a huge contourite depositional system associated with the interaction of strong Antarctic water masses with the seafloor. So far, however, only one mega slide canyon (Cabo Polonio) has been described in the Uruguayan continental slope. In this work, sedimentary processes dominating the head of this mega slide canyon are described and interpreted based on the analysis of the composition (texture and fossils) and distribution of widespread gravel along its head and thalweg. This information is integrated with acoustic (multibeam and seismic) and hydrological data. Results suggest that the evolution of the head of the canyon presents retrogressive erosion related to debris and turbidity flows. This erosion is ongoing and/or has been active during the recent past and contourite deposits are involved in headwall erosion. The pathway of gravel along the canyon and the thalweg was reconstructed. The strong flow of the South Atlantic Central Water, and its interaction with the Antarctic Intermediate Water, dominates the modern hydrology, promoting highly energetic conditions enhancing headwall erosion. This work contributes to a better understanding of the sedimentary processes connected to an mega slide canyon in the upper slope off Uruguay and located in the northernmost distribution of the South Atlantic Contourite Depositional System.